Peran UN Women terhadap Diskriminasi Perempuan Korban Isis di Irak - Natasya Aulia Putri, M. Arsy Ash Ashiddiqy, Dani Kurniawansyah (UIR Press, 2023)
This research will discuss the role of UN Women against Discrimination against Women Victims of ISIS in Iraq. Iraq is a country that is included in a dangerous country for women. This is because of discrimination against women in the country. Therefore, UN Women has a role in overcoming this problem. This research examines gender inequality that occurs in Iraq, as well as how international organizations position themselves as international relations actors in this matter. This study aims to determine the role of UN Women as an international organization in overcoming the problem of discrimination in Iraq. This research uses qualitative methods and the author analyzes the problem using Clive Archer's theory about the role of international organizations. The data source used is secondary data obtained through library research. The result of this research is that there are many things that UN Women does in carrying out its role as an international organization, both the role of the instrument where UN Women makes cooperation agreements with other actors, the arena where UN Women becomes a forum or means for actors to gather, as well as the role of UN Women actors in carrying out their programs without the interference of other parties.